FDI in retailing and inflation: The case of India - Nandita Dasgupta (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
India's food price inflation is a major driving factor behind the country's overall accelerating inflation. As demonstrated by experiences of other countries, the recent move of the Indian Government to allow FDI in multi-brand retailing is a step in the right direction, transforming the way perishable agricultural produce is acquired, stored, preserved, and marketed – and thus helping to control India's persistent food inflation.
Keywords: 330